Positive pole piece as well as preparation method and application thereof

By using conductive polymer and polytetrafluoroethylene together as a binder in the dry positive electrode sheet, and through ball milling and high and low speed stirring treatment, a conductive network is formed, which solves the problems of low battery density, low conductivity and short service life of the dry positive electrode sheet, and improves the conductivity and cycle life.

CN119852315APending Publication Date: 2025-04-18XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510051053.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18

Smart Images

  • Figure BDA0005239956600000061
    Figure BDA0005239956600000061
  • Figure BDA0005239956600000071
    Figure BDA0005239956600000071
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a positive pole piece as well as a preparation method and application thereof. The positive pole piece comprises the following raw materials in parts by weight: 95-98 parts of a positive active material, 0.5-1.5 parts of polytetrafluoroethylene and 0.5-2.5 parts of a conductive polymer. The positive pole piece has the beneficial effects that the conductive polymer in the positive pole piece can serve as a binder together with polytetrafluoroethylene (PTFE), the dosage of the polytetrafluoroethylene (PTFE) is reduced, the side reaction of the polytetrafluoroethylene (PTFE) is reduced, and meanwhile, the conductive polymer can coat the surface of the positive active material, so that a conductive network is more easily formed, and the service life of the positive pole piece is prolonged. The conductivity and the cycle life of the positive plate are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a positive electrode sheet and a preparation method and application thereof. Background Art

[0002] In recent years, lithium-ion batteries have attracted much attention in the fields of electric vehicles and energy storage due to their excellent performance and wide range of application scenarios. At present, lithium-ion batteries are mostly prepared by wet process, which is simple and mature, and is the choice of most battery manufacturers. However, wet process batteries require the use of N-methylpyrrolidone NMP, which is potentially harmful, and solvents such as NMP or water will cause holes in the pole piece during the drying process, which has a negative impact on the uniformity and energy density of the pole piece.

[0003] The dry electrode process uses polytetrafluoroethylene (PTFE) fiberized film to manufacture the electrode. It does not require any solvent, saves the process of solvent drying and recovery, saves equipment investment costs and production costs, and avoids the generation of holes during solvent evaporation. Compared with the wet method, it has obvious advantages. However, PTFE has a low potential (about 0.7-1.0V vs Li + / Li) will react with lithium, consume battery active materials, and reduce battery energy density and service life; and due to the small particle size of dry-process positive electrode, traditional conductive agents are difficult to disperse evenly, resulting in low conductivity of dry-process positive electrode and reduced battery cycle life. Summary of the invention

[0004] The present application provides a positive electrode plate and a preparation method and application thereof, aiming to solve the problems of low battery capacity density, low conductivity and short service life of dry-process positive electrode plates in the prior art.

[0005] In a first aspect, the present application provides a positive electrode plate, comprising the following raw materials in parts by weight: 95-98 parts of positive electrode active material, 0.5-1.5 parts of polytetrafluoroethylene, and 0.5-2.5 parts of conductive polymer.

[0006] According to some embodiments of the positive electrode plate described in the present application, the weight ratio of the polytetrafluoroethylene to the conductive polymer is (0.25-3):1, preferably (0.5-1.5):1.

[0007] According to some embodiments of the positive electrode plate described in the present application, the positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide.

[0008] According to some embodiments of the positive electrode plate described in the present application, the conductive polymer includes one or more of polyaniline, polypyrrole and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate.

[0009] According to some embodiments of the positive electrode plate described in the present application, the conductive polymer includes poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate.

[0010] According to some embodiments of the positive electrode plate described in the present application, the positive electrode plate further includes 0-2 parts by weight of a conductive agent.

[0011] According to some embodiments of the positive electrode plate described in the present application, the conductive agent includes one or more of carbon black, graphene and carbon fiber.

[0012] The second aspect of the present application provides a method for preparing the positive electrode sheet according to the first aspect of the present application, comprising the following steps:

[0013] (1) mixing the positive electrode active material and the conductive polymer, and performing ball milling to obtain a mixed powder;

[0014] (2) The mixed powder, polytetrafluoroethylene, and optionally a conductive agent are mixed to obtain a positive electrode powder.

[0015] According to some embodiments of the positive electrode sheet preparation method described in the present application, the rotation speed of the ball milling treatment is 180-220 rpm, and the time of the ball milling treatment is 1-1.5 h.

[0016] According to some embodiments of the positive electrode sheet preparation method described in the present application, the particle size D50 of the mixed powder is 14-15 um.

[0017] According to some embodiments of the positive electrode sheet preparation method described in the present application, in step (2), the mixing includes a first mixing stage and a second mixing stage, the mixing speed of the first mixing stage is 200-500 rpm, and the mixing time of the first mixing stage is 1-2 min; the mixing speed of the second mixing stage is 2000-3000 rpm, and the mixing time of the second mixing stage is 1-3 min.

[0018] According to some embodiments of the method for preparing the positive electrode sheet described in the present application, the method further includes calendering the positive electrode powder to obtain a positive electrode film, calendering the positive electrode film onto an aluminum foil and rolling it to obtain the positive electrode sheet.

[0019] According to some embodiments of the positive electrode sheet preparation method described in the present application, the thickness of the positive electrode film is 40-50 μm.

[0020] According to some embodiments of the positive electrode sheet preparation method described in the present application, the rolling temperature is 100-160°C.

[0021] According to some embodiments of the method for preparing the positive electrode sheet described in the present application, the thickness of the positive electrode sheet is 85-100 μm.

[0022] The third aspect of the present application provides a lithium battery, comprising the positive electrode sheet described in the first aspect of the present application or the positive electrode sheet obtained by the preparation method described in the second aspect of the present application.

[0023] The beneficial effects of the present application include: the conductive polymer in the positive electrode plate described in the present application can act as a binder together with polytetrafluoroethylene (PTFE), reducing the amount of polytetrafluoroethylene (PTFE) used and reducing the side reactions of polytetrafluoroethylene (PTFE); at the same time, the conductive polymer can be coated on the surface of the positive electrode active material, making it easier to form a conductive network, thereby improving the conductivity and cycle life of the positive electrode plate. DETAILED DESCRIPTION

[0024] The following embodiments of the present invention are described in detail. The following embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0025] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0026] The embodiment of the present application provides a positive electrode plate, comprising the following raw materials in parts by weight: 95-98 parts of positive electrode active material, 0.5-1.5 parts of polytetrafluoroethylene, and 0.5-2.5 parts of conductive polymer.

[0027] The conductive polymer in the positive electrode plate described in the present application can act as a binder together with polytetrafluoroethylene (PTFE), reducing the amount of polytetrafluoroethylene (PTFE) used and reducing the side reactions of polytetrafluoroethylene (PTFE). At the same time, the conductive polymer can be coated on the surface of the positive electrode active material, making it easier to form a conductive network and improve the conductivity of the positive electrode plate.

[0028] In some embodiments of the present application, the positive electrode plate includes the following raw materials in parts by weight: 96-97 parts of positive electrode active material, 0.8-1.2 parts of polytetrafluoroethylene and 1.8-2.2 parts of conductive polymer.

[0029] In some embodiments of the present application, the positive electrode plate includes the following raw materials in parts by weight: 96 parts of positive electrode active material, 1 part of polytetrafluoroethylene and 1.8 parts of conductive polymer.

[0030] In some embodiments of the present application, the weight ratio of the polytetrafluoroethylene to the conductive polymer is (0.25-3):1, preferably (0.5-1.5):1. The weight ratio of polytetrafluoroethylene to the conductive polymer within this range can ensure that the conductive polymer fully exerts its electronic properties, while also assisting polytetrafluoroethylene in forming a cross-linked network. If there is too much conductive polymer and too little polytetrafluoroethylene, the film-forming property of the dry electrode will be affected, increasing the difficulty of processing; if there is too little conductive polymer and too much polytetrafluoroethylene, the improvement effect of the electrode conductivity will be reduced, and the ideal effect will not be achieved.

[0031] In some embodiments of the present application, the positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide.

[0032] In some embodiments of the present application, the conductive polymer includes one or more of polyaniline, polypyrrole and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate.

[0033] In some embodiments of the present application, the conductive polymer includes poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate.

[0034] In some embodiments of the present application, the positive electrode plate further includes 0-2 parts by weight of a conductive agent.

[0035] In some embodiments of the present application, the conductive agent includes one or more of carbon black, graphene and carbon fiber.

[0036] The present application also provides a method for preparing the positive electrode sheet according to the first aspect of the present application, comprising the following steps:

[0037] (1) mixing the positive electrode active material and the conductive polymer, and performing ball milling to obtain a mixed powder;

[0038] (2) The mixed powder, polytetrafluoroethylene, and optionally a conductive agent are mixed to obtain a positive electrode powder.

[0039] The preparation method described in the present application first ball-mills the positive electrode active material and the conductive polymer so that the conductive polymer can be coated on the positive electrode active material in advance. If the conductive polymer is added later for coating, on the one hand, accurate coating cannot be guaranteed, and the second PTFE will be over-fibrous during ball milling, resulting in poor film-forming properties.

[0040] In some embodiments of the present application, the rotation speed of the ball milling treatment is 180-220rpm, for example, 180rpm, 190rpm, 200rpm, 210rpm, 220rpm, etc., and the time of the ball milling treatment is 1-1.5h, for example, 1h, 1.2h, 1.3h, 1.5h, etc.

[0041] In some embodiments of the present application, the particle size D50 of the mixed powder is 14-15 um.

[0042] In some embodiments of the present application, in step (2), the mixing includes a first mixing stage and a second mixing stage, the mixing speed of the first mixing stage is 200-500rpm, such as 200rpm, 300rpm, 400rpm, 500rpm, etc., the mixing time of the first mixing stage is 1-2min, such as 1min, 1.5min, 2min, etc.; the mixing speed of the second mixing stage is 2000-3000rpm, such as 2000rpm, 2200rpm, 2400rpm, 2600rpm, 2800rpm, 3000rpm, etc., the mixing time of the second mixing stage is 1-3min, such as 1min, 2min, 3min, etc. The mixing is carried out in two stages, the first stage is preliminary mixing, the rotation speed is low to prevent PTFE fiberization; the second stage is after PTFE has been evenly dispersed, the rotation speed is increased again, and the PTFE is fiberized by shear force.

[0043] In some embodiments of the present application, the positive electrode powder is subjected to calendering treatment to obtain a positive electrode film, and the positive electrode film is calendered onto an aluminum foil and rolled to obtain the positive electrode plate.

[0044] In some embodiments of the present application, the thickness of the positive electrode film is 40-50 μm, for example, 40 μm, 45 μm, 48 μm, 50 μm, etc.

[0045] In some embodiments of the present application, the rolling temperature is 100-160°C, for example, 100°C, 120°C, 130°C, 135°C, 140°C, 150°C, 160°C, etc.

[0046] In some embodiments of the present application, the thickness of the positive electrode plate is 85-100 μm, for example, 85 μm, 90 μm, 95 μm, 100 μm, etc.

[0047] The present application also provides a lithium battery, including the positive electrode sheet described in the first aspect of the present application or the positive electrode sheet prepared by the preparation method described in the second aspect of the present application. The lithium battery described in the present application has low internal resistance, high initial efficiency, and long cycle life.

[0048] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0049] Example 1

[0050] A method for preparing a positive electrode sheet comprises the following steps:

[0051] (1) 97 g of NCM811 and 1.5 g of polyaniline (PANI) were mixed and ball-milled at 200 rpm for 1 h to obtain a mixed powder with a particle size D50 of 14 μm;

[0052] (2) adding 1 g of polytetrafluoroethylene (PTFE) and 0.5 g of carbon black to the mixed powder, stirring at a low speed of 300 rpm for 1 min to mix evenly, and then stirring at a high speed of 3000 rpm for 2 min to fiberize the PTFE to obtain a positive electrode powder;

[0053] (3) The positive electrode powder is rolled to obtain a positive electrode film with a thickness of 40 μm, and then the positive electrode film is rolled onto an aluminum foil, and then the aluminum foil is hot rolled at 120° C. to obtain a positive electrode sheet with a thickness of 85 μm.

[0054] Example 2

[0055] The difference between Example 2 and Example 1 is that the positive electrode plate described in Example 2 uses polypyrrole conductive polymer instead of polyaniline conductive polymer.

[0056] The specific steps include:

[0057] 1) 97 g of NCM811 and 1.5 g of polypyrrole (PPy) were mixed and ball-milled at 200 rpm for 1 h to obtain a mixed powder with a particle size D50 of 14 μm;

[0058] (2) adding 1 g of polytetrafluoroethylene (PTFE) and 0.5 g of carbon black to the mixed powder, stirring at a low speed of 300 rpm for 1 min to mix evenly, and then stirring at a high speed of 3000 rpm for 2 min to fiberize the PTFE to obtain a positive electrode powder;

[0059] (3) The positive electrode powder is rolled to obtain a positive electrode film with a thickness of 40 μm, and then the positive electrode film is rolled onto an aluminum foil, and then the aluminum foil is hot rolled at 120° C. to obtain a positive electrode sheet with a thickness of 85 μm.

[0060] Example 3

[0061] The only difference between Example 3 and Example 1 is that the positive electrode plate described in Example 3 uses poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate conductive polymer instead of polyaniline conductive polymer.

[0062] The specific steps include:

[0063] 1) 97 g of NCM811 and 1.5 g of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate (PEDOT:PSS) were mixed and ball-milled at 200 rpm for 1 h to obtain a mixed powder with a particle size D50 of 14 μm;

[0064] (2) adding 1 g of polytetrafluoroethylene (PTFE) and 0.5 g of carbon black to the mixed powder, stirring at a low speed of 300 rpm for 1 min to mix evenly, and then stirring at a high speed of 3000 rpm for 2 min to fiberize the PTFE to obtain a positive electrode powder;

[0065] (3) The positive electrode powder is rolled to obtain a positive electrode film with a thickness of 40 μm, and then the positive electrode film is rolled onto an aluminum foil, and then the aluminum foil is hot rolled at 120° C. to obtain a positive electrode sheet with a thickness of 85 μm.

[0066] Example 4

[0067] The only difference between Example 4 and Example 3 is that the weight ratio of polytetrafluoroethylene and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate in the positive electrode plate of Example 4 is 1.5:1.

[0068] Example 5

[0069] The only difference between Example 5 and Example 3 is that the weight ratio of polytetrafluoroethylene and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate in the positive electrode plate of Example 5 is 3:1.

[0070] Example 6

[0071] The only difference between Example 6 and Example 3 is that the weight ratio of polytetrafluoroethylene and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate in the positive electrode plate of Example 6 is 0.25:1.

[0072] Example 7

[0073] The only difference between Example 7 and Example 3 is that during the preparation of the positive electrode sheet described in Example 7, NCM811 and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate are mixed and ball-milled at 100 rpm for 1 hour.

[0074] Example 8

[0075] The only difference between Example 8 and Example 3 is that during the preparation of the positive electrode sheet described in Example 8, NCM811 and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate are mixed and ball-milled at 220 rpm for 1 hour.

[0076] Example 9

[0077] The only difference between Example 9 and Example 3 is that during the preparation of the positive electrode sheet described in Example 9, NCM811 and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate are mixed and ball-milled at 300 rpm for 1 hour.

[0078] Comparative Example 1

[0079] The difference between Comparative Example 1 and Example 3 is that: the positive electrode plate described in Comparative Example 1 does not add poly (3, 4-ethylenedioxythiophene) - polystyrene sulfonate conductive polymer during the preparation process, and the rest of the operations are the same as Example 3.

[0080] Comparative Example 2

[0081] A method for preparing a positive electrode sheet comprises the following steps:

[0082] NCM811, PVDF and conductive agent were mixed in a mass ratio of 97:1.3:1.7, and NMP was added to adjust the viscosity. After coating and rolling (3.50 g / cm 3 ) and cutting process to obtain the positive electrode sheet.

[0083] Performance study of the positive electrode sheets described in Examples 1-9 and Comparative Examples 1-2 of the present application:

[0084] 1. Test method: The positive electrode sheets, PE separators, and negative electrode sheets described in Examples 1-9 and Comparative Examples 1-2 of the present application are stacked in order to obtain an electrode assembly. The electrode assembly is placed in an outer packaging aluminum-plastic film, and a soft-pack battery is obtained through vacuum packaging, standing, and formation processes.

[0085] The preparation method of the negative electrode plate comprises the following steps: mixing artificial graphite, silicon carbon, acetylene black and styrene butadiene rubber in a mass ratio of 80:15:2:3, adding deionized water to adjust the viscosity, coating, rolling (1.60 g / cm 3 ) and cutting process to obtain the negative electrode sheet.

[0086] 2. The test results are shown in Table 1.

[0087] Among them, the first efficiency is the percentage of the test 0.33C discharge capacity divided by the 0.1C first week charging capacity;

[0088] 25℃DCIR: Let I0 be the current corresponding to 0.1C, and I1 be the current corresponding to 1C. Fresh cells that have not been tested for electrical performance are placed in a 25℃ constant temperature box for more than 1 hour, and discharged to 3V with a constant current of I0; left to stand for 10 minutes; charged with a constant current of I0 for 5 hours (the voltage at the end is recorded as U0), and then charged with a constant current of I1 for 1 second (the voltage at the end is recorded as U1).

[0089] 25℃DCIR=(U1-U0) / (I1-I0)

[0090] Cycle life: The number of cycles of 0.5C charge / 0.5C discharge until the capacity retention rate drops to 80%.

[0091] Table 1

[0092]

[0093]

[0094] It can be seen from Table 1 that: from the analysis of Examples 1-3, it can be seen that the poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate conductive polymer has excellent conductive properties in the dry ternary positive electrode system.

[0095] Analysis of Examples 3-6 shows that when the weight ratio of polytetrafluoroethylene to the conductive polymer is in the range of (0.5-1.5):1, the obtained positive electrode sheet has better conductive properties.

[0096] From the analysis of Example 3 and Examples 7-9, it can be seen that the ball milling speed is a key factor affecting the coating degree of the conductive polymer on the positive electrode active material. Incomplete coating or excessive coating is not conducive to the performance of the battery.

[0097] From Example 3 and Comparative Example 1, adding a conductive polymer can greatly improve the overall performance of the battery, and the improvement in the cycle performance is particularly obvious.

[0098] From Example 3 and Comparative Example 2, the dry-process electrode after adding the conductive polymer is closer to the wet-process electrode and has strong commercial value.

[0099] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A positive electrode sheet, characterized in that: The invention comprises the following raw materials in parts by weight: 95-98 parts of positive electrode active material, 0.5-1.5 parts of polytetrafluoroethylene and 0.5-2.5 parts of conductive polymer.

2. The positive electrode sheet according to claim 1, characterized in that: The weight ratio of the polytetrafluoroethylene to the conductive polymer is (0.25-3):1, preferably (0.5-1.5):

1.

3. The positive electrode sheet according to claim 1, characterized in that: The positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide; and / or, the conductive polymer comprises one or more of polyaniline, polypyrrole and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate; Preferably, the conductive polymer comprises poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate.

4. The positive electrode sheet according to claim 1, characterized in that: The positive electrode plate also includes 0-2 parts by weight of a conductive agent; Preferably, the conductive agent includes one or more of carbon black, graphene and carbon fiber.

5. The method for preparing the positive electrode sheet according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing the positive electrode active material and the conductive polymer, and performing ball milling to obtain a mixed powder; (2) The mixed powder, polytetrafluoroethylene, and optionally a conductive agent are mixed to obtain a positive electrode powder.

6. The method for preparing the positive electrode sheet according to claim 5, characterized in that: The rotation speed of the ball milling treatment is 180-220 rpm, and the time of the ball milling treatment is 1-1.5 h; And / or, the particle size D50 of the mixed powder is 14-15 um.

7. The method for preparing a positive electrode sheet according to claim 5, characterized in that: In step (2), the mixing includes a first mixing stage and a second mixing stage, the mixing speed of the first mixing stage is 200-500 rpm, and the mixing time of the first mixing stage is 1-2 min; the mixing speed of the second mixing stage is 2000-3000 rpm, and the mixing time of the second mixing stage is 1-3 min.

8. The method for preparing the positive electrode sheet according to claim 5, characterized in that: The method also includes calendering the positive electrode powder to obtain a positive electrode film, calendering the positive electrode film onto an aluminum foil and rolling it to obtain the positive electrode plate.

9. The method for preparing the positive electrode sheet according to claim 8, characterized in that: The thickness of the positive electrode film is 40-50 μm; And / or, the rolling temperature is 100-160°C; And / or, the thickness of the positive electrode plate is 85-100 μm.

10. A lithium battery, characterized in that: It comprises the positive electrode sheet described in any one of claims 1 to 4 or the positive electrode sheet obtained by the preparation method described in any one of claims 5 to 9.

Citation Information

Patent Citations

  • Positive electrode material and battery

    CN106328950A

  • Oxide positive electrode material coated with conductive polymer through ball milling and preparation method and application of oxide positive electrode material

    CN114361395A

  • Positive pole piece without conductive agent, lithium battery and preparation method of positive pole piece

    CN115241410A

  • Pole piece, manufacturing method thereof and battery

    CN116230868A

  • Anode material and battery

    WO2016202276A1